2007 IEEE Sensors 2007
DOI: 10.1109/icsens.2007.4388620
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Straight Tube Fluid Density Sensor

Abstract: In this paper, a new and simple silicon straight tube is tested as a fluid density sensor. The tube structure has a hexagonal cross section. The fabrication process consists of anisotropic silicon etching and silicon fusion bonding. A tube structure with a length of 2.65 cm was tested. The sample volume is 9.3 µL. The first three modes of vibrations were investigated with a laser Doppler vibrometer for air and five liquid mixtures. The fluid density sensitivity of each mode was measured and the average was −25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Note that this method can be applied to the devices with a flake thickness higher than the Debye length (~7.2 nm at this carrier concentration or doping regime). Series resistance: The series resistance, similar to an inversion-mode MOSFET in [4], can be extracted from the yintercept of R tot =V ds /I d vs. 1/(V gs -V fb ) in linear accumulation regime (V ds <V gs -V fb ), see Fig. 4, assuming accumulation as the dominant conduction mechanism in comparison to bulk conduction.…”
Section: D Mosfet Operation Of a Fully-depleted Bulk Mosmentioning
confidence: 99%
“…Note that this method can be applied to the devices with a flake thickness higher than the Debye length (~7.2 nm at this carrier concentration or doping regime). Series resistance: The series resistance, similar to an inversion-mode MOSFET in [4], can be extracted from the yintercept of R tot =V ds /I d vs. 1/(V gs -V fb ) in linear accumulation regime (V ds <V gs -V fb ), see Fig. 4, assuming accumulation as the dominant conduction mechanism in comparison to bulk conduction.…”
Section: D Mosfet Operation Of a Fully-depleted Bulk Mosmentioning
confidence: 99%
“…The two subproblems consist of determining the scalar potentials ðiÞ ðr; ; tÞ and ðiÞ ðr; ; tÞ satisfying the Helmholtz Eqs. (6) and (7). Introducing a new auxiliary variable ¼ j ffiffiffiffiffi j!…”
Section: Formulation For Compressible Viscous°uidsmentioning
confidence: 99%
“…3 Like any other technology, to be able to implement microstructures and micro°uidic, 4,5 suitable production techniques have to be discovered. Microstructures and micro°uidics systems can have various applications in microresonators 6 and in targeted drug delivery devices and, in view of their excellent mechanical properties and hollow geometry. Bhirde 7 showed that the hollow geometry, for example, can be considered as drug delivery system in targeted therapy which results in a signi¯cant decrease in tumor size.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Corman [ 7 ] presented a fully low-pressure encapsulated and closed-loop operated resonant fluid density sensor, where the required sample volume was only 35 µL. A new simple silicon straight tube was tested as a fluid density sensor in the study of Najmzadeh [ 8 ]; the length of the proposed tube was 2.65 cm, and the volume of the fluid sample was only 9.3 µL. The micro-cantilever is one of most common structures used for MEMS vibration devices, as it is simple and reliable [ 9 ].…”
Section: Introductionmentioning
confidence: 99%